ChemInform Abstract: Catalytic Asymmetric [3 + 3] Annulation of Cyclopropanes with Mercaptoacetaldehyde. Issue 45 (October 2016) - Fu, Xuan; Lin, Lili; Xia, Yong; Zhou, Pengfei; Liu, Xiaohua; Feng, Xiaoming
Abstract: The highly diastereoselective and enantioselective title reaction of aryl substituted cyclopropyl ketones with mercaptoacetaldehyde is described.